Association between driving pressure and development of postoperative pulmonary complications in patients undergoing mechanical ventilation for general anaesthesia: a meta-analysis of individual patient data. Issue 4 (April 2016) - Neto, Ary Serpa; Hemmes, Sabrine N T; Barbas, Carmen S V; Beiderlinden, Martin; Fernandez-Bustamante, Ana; Futier, Emmanuel; Gajic, Ognjen; El-Tahan, Mohamed R; Ghamdi, Abdulmohsin A Al; Günay, Ersin; Jaber, Samir; Kokulu, Serdar; et al.
Summary: Background: Protective mechanical ventilation strategies using low tidal volume or high levels of positive end-expiratory pressure (PEEP) improve outcomes for patients who have had surgery. The role of the driving pressure, which is the difference between the plateau pressure and the level of positive end-expiratory pressure is not known. We investigated the association of tidal volume, the level of PEEP, and driving pressure during intraoperative ventilation with the development of postoperative pulmonary complications. Methods: We did a meta-analysis of individual patient data from randomised controlled trials of protective ventilation during general anesthaesia for surgery published up to July 30, 2015. The main outcome was development of postoperative pulmonary complications (postoperative lung injury, pulmonary infection, or barotrauma). Findings: We included data from 17 randomised controlled trials, including 2250 patients. Multivariate analysis suggested that driving pressure was associated with the development of postoperative pulmonary complications (odds ratio [OR] for one unit increase of driving pressure 1·16, 95% CI 1·13–1·19; p<0·0001), whereas we detected no association for tidal volume (1·05, 0·98–1·13; p=0·179). PEEP did not have a large enough effect in univariate analysis to warrant inclusion in the multivariate analysis. In a mediator analysis, driving pressure was the only significant mediator of the effects of protective ventilation on development of pulmonary complications (p=0·027). In two studies that compared low with high PEEP during low tidal volume ventilation, an increase in the level of PEEP that resulted in an increase in driving pressure was associated with more postoperative pulmonary complications (OR 3·11, 95% CI 1·39–6·96; p=0·006). Interpretation: In patients having surgery, intraoperative high driving pressure and changes in the level of PEEP that result in an increase of driving pressure are associated with more postoperative pulmonary complications. However, a randomised controlled trial comparing ventilation based on driving pressure with usual care is needed to confirm these findings. Funding: None.